Students’ Opinion towards the Use of Skimming and Scanning Techniques for TOEFL in Reading Comprehension - Asri Mawarni; Muhammad Usman (English LAnguage Study and TEaching, 2022)
The aim of this study is to know students’ opinion in using skimming and scanning techniques in reading comprehension of TOEFL test. This research was conducted based on a quantitative descriptive research design involving 30 English department students of Serambi Mekkah University from semester 7, 9, and 11. In collecting the data, the writers used a questionnaire which consists of 12 items. The findings indicated that 93.34% of students agree that both skimming and scanning techniques eased them in answering reading comprehension questions on the TOEFL test. Furthermore, 96.67% of students claimed that using skimming and scanning were effective in answering reading comprehension questions on the TOEFL test. It can be concluded that the students’ opinion towards the use of skimming and scanning is positive.